"I am hesitant to visit the doctor unless absolutely necessary": A qualitative study of delayed care, avoidance of care, and telehealth experiences during the COVID-19 pandemic. Issue 32 (12th August 2022) - Moore, Ramey; Purvis, Rachel S.; Hallgren, Emily; Reece, Sharon; Padilla-Ramos, Alan; Gurel-Headley, Morgan; Hall, Spencer; McElfish, Pearl A.
Abstract : The COVID-19 pandemic has disrupted the health care system, resulting in decreased health care utilization. During the pandemic, some patients chose to postpone clinic visits or avoid them altogether while health care providers concurrently scaled back their services. As a result, health care has shifted to a greater reliance on telehealth and virtual care. This study uses a qualitative descriptive design, focused on providing summaries of participant experiences of health care and telehealth utilization during the COVID-19 pandemic. Three primary themes emerged during analysis: delayed health care, avoidance of care, and experiences of telehealth. Sub-themes of delayed health care included care delays and scheduling difficulties. Participants reported avoidance of health care due to fear of COVID-19 infection, as well as general changes to care-seeking behaviors. Participants also reported positive experiences with telehealth, with some respondents noting limitations of telehealth systems, such as limitations on procedures and patient-centered monitoring of chronic illness. Our findings support studies that have found both health care delays and changes in health care utilization patterns during the pandemic. Most importantly, this study expands the literature concerning links between fear of COVID-19 and altered care-seeking behaviors, which is the first study to do so focusing on these concerns in the participants' own words. Finally, while telehealth is promising in preserving continuity of care during pandemics, long-term integration into the health care system is not without challenges, and this study provides insights into how patients experienced telehealth during COVID-19 in their own words. Data collection, survey design, and research priorities for this study were based on input from ongoing community partnerships.